The effect of financial development on per capita income: A panel data analysis for heterogeneous countries between 1980 and 2020 - Felipe Massafera; Luciano Ferreira Gabriel (PSL Quarterly Review)
This paper aims to investigate the relationship between the development of the financial market and per capita income. For this, panel data methods were used to analyze proxy variables of depth, risk and liquidity of the financial system for a heterogeneous sample of 95 countries from 1980 to 2020. The results suggest that while depth and liquidity of the financial system are positively related to per capita income, the risk level of the financial system is negatively related to it. Furthermore, bank credit was shown to be more significant in increasing the level of per capita income for developing countries. In developed countries, however, capital market variables most affected per capita income.